Prophylactic dendritic cell vaccination in antitumor immune response and tumor growth in a breast cancer mouse model (Research, Society and Development, 2021)
Dendritic cell vaccines have demonstrated promising results for poorly immunogenic tumors, which may promote the generation of better immune responses in the tumor microenvironment. However, the vaccine has little been evaluated as a prophylactic option. Therefore, this study evaluates the influence of prophylactic dendritic cell vaccination on the antitumor immune response in the tumor microenvironment and on tumor growth, in an experimental model with breast cancer induced by 4T1. Therefore, Balb/c mice were separated into a vaccinated group and an unvaccinated group. Dendritic cell vaccine was differentiated and matured ex vivo from bone marrow. During the experimental period, the tumor volumes were checked periodically. The tumors were evaluated for immune cells (helper T lymphocytes and cytotoxic T lymphocytes), helper T cells (Th1, Th2, Th17, and Treg), TNF-α, and IFN-γ synthesis by Th1 and cytotoxic T lymphocytes. The vaccinated group had decreased tumor volume (14.0, 0-131.7) compared to the unvaccinated group (89.59, 0.1250-459.6) (p=0.0421). The Th1, Th2, Th17, Treg, cytotoxic T subtypes, including TNF-α and IFN-γ produced by Th1 and T cytotoxic, showed a significant increase in the vaccinated group, as did the balance of Th1/Th2 and Th1/Treg. The results showed that prophylactic vaccination with dendritic cells showed a considerable antitumor effect in the studied model by promoting an increase in the activation of important cells in the immune response and a reduction in tumor volume. The data provide evidence for timely activation of immune surveillance in the absence of tumor burden.